The Hammer and the Anvil : the convergence of United States and South African foreign policies during the Reagan and Botha Administrations - Hendrix, Michael Patrick (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.